PERAN DAN PARTISIPASI MASYARAKAT DALAM UPAYA PEMANFAATAN CAGAR BUDAYA DI KABUPATEN BONDOWOSO SEBAGAI SUMBER BELAJAR SEJARAH LOKAL DAN ASET UNGGULAN DAERAH - Blasius Suprapta (Jurnal Pendidikan Sejarah Indonesia, 2020)
Bondowoso, as one of the regions of East Java Province, has the potential of cultural heritage from the various era: megalithic, Hindhu-Buddhist, colonial, and the struggle for the defense of Indonesian independence. However, the potential of cultural heritage, which is known to be spread throughout the district (kecamatan) in Bondowoso, has not been utilized as a source of local history instruction or as a vital asset of the region. For this reason, it is necessary to find a solution for modeling the use of cultural heritage as a source of historical learning and study of superior regional assets to foster the participation of local communities based on the preservation of cultural heritage for the welfare of the communities around the cultural heritage. The method used is to adopt the modeling of the use of cultural heritage, namely Malang Kembali event, the colorful village event of Jodipan Village, Malang City, the development of revitalization of the Majapahitan house in Trowulan and the Mount Pawitra adventure event. The results of the study show that the four models are suitable to be applied in Bondowoso to foster the role of the community around cultural heritage for the use of cultural heritage as a source of learning of Local History and superior regional assets in Bondowoso Regency, based on the preservation of cultural heritage.